A method to assess the loss of a dipole antenna for ultra‐high‐field MRI. Issue 3 (19th June 2017) - Chen, Gang; Collins, Christopher M.; Sodickson, Daniel K.; Wiggins, Graham C.
Abstract : Purpose: To describe a new bench measurement based on quality ( Q ) factors to estimate the coil noise relative to the sample noise of dipole antennas at 7 T. Methods: Placing a dipole antenna close to a highly conductive sample surrogate (HCSS) greatly reduces radiation loss, and using Q HCSS gives a more accurate estimate of coil resistance than Q unloaded . Instead of using the ratio of unloaded and sample‐loaded Q factors, the ratio of HCSS‐loaded and sample‐loaded Q factors should be used at ultra‐high fields. A series of simulations were carried out to analyze the power budget of sample‐loaded or HCSS‐loaded dipole antennas. Two prototype dipole antennas were also constructed for bench measurements to validate the simulations. Results: Simulations showed that radiation loss was suppressed when the dipole antenna was HCSS‐loaded, and coil loss was largely the same as when the dipole was loaded by the sample. Bench measurements also showed good alignment with simulations. Conclusions: Using the ratio Q HCSS / Q loaded gives a good estimate of the coil loss for dipole antennas at 7 T, and provides a convenient bench measurement to predict the body noise dominance of dipole antenna designs. The new approach also applies to conventional surface loop coils at ultra‐high fields. Magn Reson Med 79:1773–1780, 2018. © 2017 International Society for Magnetic Resonance in Medicine.